Encapsulation of Phase Change Materials Using Layer-by-Layer Assembled Polyelectrolytes - Qiangying Yi; Gleb B. Sukhorokov; Jin Ma; Xiaobo Yang; Zhongwei Gu (International Journal of Polymer Science)
Phase change materials absorb the thermal energy when changing their phases (e.g., solid-to-liquid) at constant temperatures to achieve the latent heat storage. The major drawbacks such as limited thermal conductivity and leakage prevent the PCMs from wide application in desired areas. In this work, an environmentally friendly and low cost approach, layer-by-layer (LbL) assembly technique, was applied to build up ultrathin shells to encapsulate the PCMs and therefore to regulate their changes in volume when the phase change occurs. Generally, the oppositely charged strong polyelectrolytes Poly(diallyldimethylammonium chloride) (PDADMAC) and Poly(4-styrenesulfonic acid) sodium salt (PSS) were employed to fabricate multilayer shells on emulsified octadecane droplets using either bovine serum albumin (BSA) or sodium dodecyl sulfate (SDS) as surfactant. Specifically, using BSA as the surfactant, polyelectrolyte encapsulated octadecane spheres in size of ∼500 nm were obtained, with good shell integrity, high octadecane content (91.3% by mass), and good thermal stability after cycles of thermal treatments.